Implementing Islamic Religious Education for Indonesian Migrant Workers in Riyadh: Community Support, Digital Adaptation, and Program Sustainability - Khairuddin Saleh Baharuddin; Tri Astuti; M. Nur Kholis; Baihaki; Imam Hambali; Ahamakosee Kasor (Universitas Islam KH. Achmad Muzakki Syah Jember, 2026)
The increasing number of Indonesian migrant workers has intensified the need for accessible and sustainable Islamic religious education that supports both spiritual development and social well-being in overseas settings. However, limited research has examined how such educational initiatives are implemented within migrant communities and sustained under the constraints of transnational labor conditions. This study explores the implementation of Islamic religious education among Indonesian migrant workers in Riyadh, Saudi Arabia, focusing on community support, digital adaptation, and program sustainability. Employing a qualitative instrumental case study, data were collected through semi-structured interviews, participant observation, and document analysis involving migrant workers, religious educators, community leaders, and institutional representatives. The data were analyzed using Reflexive Thematic Analysis. The findings indicate that Islamic religious education functions as an adaptive community-based learning ecosystem supported by collaboration among migrant organizations, mosques, families, and the Indonesian Embassy. Digital communication platforms complement face-to-face learning, expanding participation despite occupational and geographical constraints. Nevertheless, irregular working schedules, limited mobility, financial challenges, and inconsistent attendance continue to affect long-term program sustainability. This study contributes to the literature by conceptualizing Islamic religious education as an adaptive diaspora learning ecosystem shaped by community engagement, institutional collaboration, and digital innovation. The findings provide practical insights for policymakers and community organizations seeking to strengthen sustainable religious education for migrant communities.